REVIEW OF ISLAMIC ECONOMIC LAW IN THE FINANCING SYSTEM OF MJS PRODUCTS AT KPPS BINA SYARIAH UMMAH SUGIO BRANCH - Rofiqoh, Relita; Afsal, Hamzah Maulana (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2024)
Cooperatives are a collection of several members who produce common goals. The sources of cooperative funds are mandatory dues, principal dues, and voluntary dues. This research applies field research. There are 2 data sources, namely primary data sources (the main source and directly obtained from the research site, namely interviews) and secondary data sources (books, journals, legislation, and other literature studies). The data collection methods used are observation, interviews, and documentation. Analysis of data collection in the form of reducing, analyzing, and drawing conclusions. The results of the research on the Practice of Islamic Economic Law Review in the MJS Product Financing System (Multi Jasa Sehatera) at Kpps Bina Syariah Ummah Sugio Branch are The implementation of the ijarah contract on MJS products at Kpps Bina Syariah Ummah Sugio Branch is not by the DSN MUI Fatwa at Number 09/DSN- MUI/IV/2000 because the fatwa explains that the ijarah contract is a contract in the form of a lease between the owner and the tenant and the compensation is in the form of rent from the item (ujrah) not profit sharing. Whereas in the MJS product, there is profit sharing, which is the sharing of profits from the results of its business or from the results of loans that have been given. So MJS products are not by the DSN MUI fatwa. Researchers suggest that MJS products are by the MUI fatwa, so the rent is in the form of goods or services that can be taken advantage of, not in the form of money, and at the end of the rental period there is no such thing as profit sharing but in the form of paying rent from the goods or services being rented.